Quality Control Analysis to Minimize the Risk of Defective Products Using Statistical Process Control (SPC) and Failure Modes and Effect Analysis (FMEA) Methods (Case Study: PT XYZ Samarinda) - Dahlia, Azura; Tongsuku, La Ode Ahmad Safar; Gunawan, Suwardi (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
PT. XYZ is a company that produces plywood. The issue faced by this company is the increasing risk of defective plywood products resulting from the production process. This research conducts a risk analysis of rejected defective products using the Statistical Process Control (SPC) method to identify the types of defects and their causes, as well as the Failure Mode and Effect Analysis (FMEA). Based on production data from January 2022 to April 2023, PT. XYZ Samarinda has produced 6,629,815 plywood pieces, with 356,137 rejected defective products. There are 10 types of defects, namely delamination defects, blisters, 2x process fractures, impacts, cores that are too narrow, patches, defective sander F/B, F/B too narrow, defective press F/B, and uneven cores. The results obtained from the SPC method indicate that there are four priority defect types: delamination defects, blisters, 2x process fractures, and impacts. According to the FMEA method, the most risky cause for delamination defects is applying a layer of adhesive that is too thin, with an RPN value of 280. The most risky cause for blister defects is an excessively high adhesive dose, with an RPN value of 180. The most risky cause for 2x process fractures is excessive pressure during the core scratching process that penetrates the F/B, with an RPN value of 210. The most risky cause for impact defects is careless workers when moving plywood lots using a cart, with an RPN value of 144. Subsequently, improvement proposals are made using the 5W+1H method to determine the causes of defects and the necessary improvements that the company should undertake.